# Convolution not commutative for this case?

Discussion in 'Homework Help' started by jp1390, Oct 6, 2011.

1. ### jp1390 Thread Starter Member

Aug 22, 2011
45
2
Hi all, just needing some clarification on this question, or just another pair of eyes to check if I am doing this correctly. I am wanting to compute the convolution of v(t) and g(t). In doing so I wanted to try to test commutativity, but found that it wasn't working out.

When I tried the first convolution, I yielded the correct result over the desired regions of overlap, but for the second, I did not.

Method 1
$y(t) = g(t)\ast v(t) = \int_{-\infty}^{\infty}g(\tau)v(\tau-t)d\tau$

Method 2
$y(t) = v(t)\ast g(t) = \int_{-\infty}^{\infty}v(\tau)g(\tau-t)d\tau$ (did not receive correct result)

Region 1

t <= 0;
$y(t_{1}) = 0$

Region 2

t >= 0 and (t-2) <= 0
0 <= t <= 2;

$y(t_{2}) = \int_{0}^{t}(exp{-\tau})(2exp{2(\tau -t)})d\tau$

$= 2exp{-2t}\int_{0}^{t}exp{\tau}d\tau$

$=2exp{-2t}(exp{t} - 1)$

The answer for this region should be:

$y(t_{2}) = 2exp{-t}(1 - exp{-t})$

I got the correct result when I flipped and shifted v(t) as in Method 1, which is weird because they should be commutative.

Can anyone see where I went wrong?

Thanks,
JP

2. ### Zazoo Member

Jul 27, 2011
114
43
These two results are the same, they are just factored differently. i.e if you distribute the outside term both are equal to:
$y(t) = 2exp{-t} - 2exp{-2t}$

3. ### jp1390 Thread Starter Member

Aug 22, 2011
45
2
Whoa, I must have had a major brain fart. Thanks haha